The journey from prison to community: developing identity, meaning and belonging with men in the UK - Shingler, Jo; Stickney, Jennifer (Routledge, 2024)
"The Journey from Prison to Community: Developing Identity, Meaning and Belonging with Men in the UK provides a practical guide for practitioners working with men to successfully make the transition between prison and the community. This is an essential read for professionals working in a range of settings across prison and community environments, while the wide variety of professional experience represented in the book broadens its appeal to forensic and clinical psychologists, occupational therapists, probation officers, prison staff and those working in the third sector. It is also valuable resource for qualified professionals, those in training, support roles, and managers involved in planning strategy and service delivery"--